The Effect Of Work Discipline, Work Environment And Work Motivation On Employee Productivity At PT VME PROCESS In Batam - Rhionald Oktofid Riang Hepat; Imelda Tamba; Pilifus Junianto; Josepin Harianja (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2026)
This study aims to determine the effect of work discipline, work environment, and work motivation both partially and simultaneously on employee productivity at PT VME PROCESS in Batam City. This research was conducted using a quantitative research method with a sample size of 60 respondents and data collection using questionnaires. The results of the partial test (t) found that the calculated t value for work discipline was (-0.230) < t table 2.000 with a significance level of (0.819) > α (0.05), indicating that work discipline does not have a positive and significant effect on work productivity. Then, the calculated t value for work environment was 5.406 > t table 2.000 with a significance level of (0.000) < α (0.05), showing that the work environment has a positive and significant effect on work productivity. After that, the calculated t value for work motivation was 1.901 < t table 2.000 with a significance level of (0.062) > α (0.05), meaning that work motivation does not have a positive and significant effect on work productivity. From the simultaneous test (f), it is known that the f calculated value for work discipline, work environment, and work motivation is 25.958 > f table 2.18, with a significance level of 0.000 < 0.05. This shows that the variables of work discipline, work environment, and work motivation simultaneously have a positive and significant effect on employee work productivity at PT VME PROCESS in Batam City.